Novel in-home COVID-19 vaccination program for vulnerable populations using public-private collaboration - Zhou, Megan S.; Attia, Cyrus; Barnes, Melynda; Chen, Tina; Chlada, Katie; Doukas, Mel; John, Julia; Kanter, Julia; Kim, Dayna; Qualliotine, Kerry; Stein, Jillian; Stern, Kevin; et al. (Frontiers in Public Health, 2022)
Background The continued emergence of new COVID-19 variants highlights the importance of vaccination in the effort to reduce disease transmission and burden. The objective of this study is to evaluate the processes and outcomes associated with a novel in-home COVID-19 vaccination program aimed at vaccinating high-risk populations in New York, USA. Methods To evaluate program processes, we described the program itself and reflected on some key lessons learned. To evaluate program outcomes, we analyzed data reported by vaccine recipients. These outcomes included the percentage of vaccine recipients that successfully received the full course of vaccinations, and the demographic and health characteristics of vaccine recipients. We additionally assessed demographic differences in motivations for receiving in-home care, using chi-squared tests to assess statistical significance. Data were collected and reported via dynamic online intake forms. Results The median age of vaccine recipients was 79 ± SD 9.0 years. The oldest vaccine recipient was 107 years old. Of those with non-missing data, more than half of vaccine recipients were female (63%), identified as part of a racial/ethnic minority (66%), reported an annual income of < $25,000 (58%), and received a high school degree or less (68%). Most vaccine recipients reported having one or more health conditions associated with increased risk of severe COVID-19 disease (72%). Vaccine recipients were most likely to report receiving in-home vaccination because they were home-bound due to disability. Motivations for receiving in-home vaccination differed by demographic subgroup. Conclusion The population receiving vaccinations from this in-home care delivery program comprised seniors who were mostly female and non-white, indicated socioeconomic vulnerability, and reported one or more COVID-related health conditions; this signified that the program met its goal of vaccinating those most at risk for severe COVID-19 disease.